Profile of cancer patients’ seen at Korle Bu teaching hospital in Ghana (A cancer registry review) - Calys-Tagoe, Benedict NL (BioMed Central, 2014)
BACKGROUND: Though cancer has become a major source of morbidity and mortality globally, few countries in Sub Saharan Africa have data on cancer incidence. This study aims to describe the profile of cancers seen at the Korle Bu teaching hospital which is a major referral centre in Ghana for cancers and other health conditions. Data for the study was obtained from the cancer registry of the hospital and covered the period from January 2012 to December 2012. The public health unit actively collects data on all cancer cases presenting to any department/unit of the hospital to feed the cancer registry. RESULTS: A total of 1136 patients with cancer were studied. Their ages ranged from 1 year to 92 years with a mean of 52.3 ± 15.9 years and a median of 54 years. Patients were predominantly female (70.2%) and majority had attained secondary level of education or higher. The most prevalent cancers seen in men were those of prostate, pharynx and colorectal while in the females, the corresponding cancers were breast, cervix and uterus. CONCLUSIONS: Breast and prostate cancers were the commonest among females and males respectively who presented with cancer at the Korle Bu teaching hospital in 2012.